Microvascular Disease, Peripheral Artery Disease, and Amputation. Issue 6 (6th August 2019) - Beckman, Joshua A.; Duncan, Meredith S.; Damrauer, Scott M.; Wells, Quinn S.; Barnett, Joey V.; Wasserman, David H.; Bedimo, Roger J.; Butt, Adeel A.; Marconi, Vincent C.; Sico, Jason J.; Tindle, Hilary A.; Bonaca, Marc P.; et al.
Abstract : Background: The mechanism of adverse limb events associated with peripheral artery disease remains incompletely understood. We investigated whether microvascular disease is associated with amputation in a large cohort of veterans to determine whether microvascular disease diagnosed in any location increases the risk of amputation alone and in concert with peripheral artery disease. Methods: Participants in the Veterans Aging Cohort Study were recruited from April 1, 2003 through December 31, 2014. We excluded participants with known prior lower limb amputation. Using time-updated Cox proportional hazards regression, we analyzed the effect of prevalent microvascular disease (retinopathy, neuropathy, and nephropathy) and peripheral artery disease status on the risk of incident amputation events after adjusting for demographics and cardiovascular risk factors. Results: Among 125 674 veterans without evidence of prior amputation at baseline, the rate of incident amputation over a median of 9.3 years of follow-up was 1.16 per 1000 person-years, yielding a total of 1185 amputations. In time-updated multivariable-adjusted analyses, compared with those without peripheral artery disease or microvascular disease, microvascular disease alone was associated with a 3.7-fold (95% CI, 3.0–4.6) increased risk of amputation; peripheral artery disease alone conferred a 13.9-fold (95% CI, 11.3–17.1) elevated risk of amputation; and the combination of peripheral artery disease and microvascular disease was associated with a 22.7-fold (95% CI, 18.3–28.1) increased risk of amputation. Conclusions: Independent of traditional risk factors, the presence of microvascular disease increases the risk of amputation alone and synergistically increases risk in patients with peripheral artery disease. Further research is needed to understand the mechanisms by which this occurs. Abstract : Supplemental Digital Content is available in the text.